Individual differences in working memory capacity and search efficiency. - Miller, Ashley L.; Unsworth, Nash (Memory & Cognition, 2018)
In two experiments, we examined how various learning conditions impact the relation between working memory capacity (WMC) and memory search abilities. Experiment 1 employed a delayed free recall task with semantically related words to induce the buildup of proactive interference (PI) and revealed that the buildup of PI differentially impacted recall accuracy and recall latency for low-WMC and high-WMC individuals. Namely, the buildup of PI impaired recall accuracy and slowed recall latency for low-WMC individuals to a greater extent than what was observed for high-WMC individuals. To provide a circumstance in which previously learned information remains relevant over the course of learning, Experiment 2 required participants to complete a multitrial delayed free recall task with unrelated words. Results revealed that with increased practice with the same word list, WMC-related differences were eventually eliminated in interresponse times (IRTs) and recall accuracy, but not recall latency. Thus, despite still accumulating larger search sets, low-WMC individuals searched LTM as efficiently as high-WMC individuals. Collectively, these results are consistent with the notion that under normal free recall conditions, low-WMC individuals search LTM less efficiently than do high-WMC individuals because of their reliance on noisy temporal-contextual cues at retrieval. However, it appears that under conditions in which previously learned items remain relevant at recall, this tendency to rely on vague self-generated retrieval cues can actually facilitate the ability to accurately and quickly recall information.